Botany, secondary metabolites, therapeutic effects and toxicity of Ferula persica: A review - Fatemeh Hoseinpour; Zahra Lorigooini (Islamic Azad University, Shahrekord Branch, 2023)
Background & Aim: Ferula persica is a medicinal plant belonging to the Apiaceae family and grows in some provinces of Iran, including Mazandaran, Tehran, Semnan, Alborz, and Qazvin. The plant is traditionally used as an expectorant, antispasmodic, anti-bloating and laxative, also it is used to treat indigestion with bloating and constipation, neurologic diseases, epilepsy, and various pain, especially joint pain. Due to the value and importance of F. persica in traditional medicine and its beneficial pharmacological effects, this review aimed to investigate the findings on the ethnobotany, phytochemistry, traditional uses, and pharmacological effects of this medicinal plant published up to 2022. Experimental: The information and findings in this review were obtained via electronic search using Google Scholar, Pubmed, Science Direct, Wiley Online, and Taylor & Francis, as well as relevant books. Results: Various studies have shown that F. persica contains secondary metabolites such as coumarin, sulfur-containing compounds, steroids such as stigma-esterol, sitosterol, monoterpene and sesquiterpene, also numerous pharmacological activities including antitumor, anti-Alzheimer, antiepileptic, analgesic, anti-inflammatory, antibacterial, and antigenotoxic, about the plant have been reported. Recommended applications/industries: Due to high-value components, wide application in traditional medicine, and various pharmacological effects, F. persica may be addressed as a source of multiple herbal medicinal compounds.